Case Study : D’Roi F&B Industries / Nurul Syahirah Hasbi - Hasbi, Nurul Syahirah (2020)
D’Roi F&B Industries is the manufacturer for instant paste and maker of “Bawang Goreng”. All the recipe for instant paste are created by the owner herself